A Plurisensorial Device to Support Human Smell in Hazardous Environment and Prevent Respiratory Disease. (4th April 2019) - Ferraro, Venere; Rampino, Lucia; Stepanovic, Mila
Abstract : Products embedded with wearable technologies can be a useful tool to support humans' senses in situations where they can be insufficient, mistaken, or misleading. In this article, we discuss the findings of a two-year Transnational European Research Project named "POD: Plurisensorial Device to Prevent Occupational Disease." The research was based on the evidence that human senses are not always reliable in making objective judgments. The specific field of application was coating plant, an environment that exposes workers to the risk of inhaling dangerous particles. The results obtained in the first part of the research pointed out that workers, largely relying on their sense of smell, which instead is often untrustworthy, do not protect themselves enough. Based on this ground, we designed a wearable system for providing workers with objective data both on their respiration activity and on the quality of the air in the working environment, with the ultimate goal of engaging them in wearing their personal protecting equipment (PPE). The article describes the development and testing of the solution; an example of how wearable technologies can enhance senses and improve workers' health.